2012
DOI: 10.1175/jcli-d-11-00290.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate Sensitivity of the Community Climate System Model, Version 4

Abstract: Abstract.Equilibrium climate sensitivity of the Community Climate System Model Version 4 (CCSM4) is 3.20• C for 1• horizontal resolution in each component. This is about a half degree Celsius higher than in the previous version (CCSM3). The transient climate sensitivity of CCSM4 at 1• resolution is 1.72• C, which is about 0.2 • C higher than in CCSM3. These higher climate sensitivities in CCSM4 cannot be explained by the change to a preindustrial baseline climate. We use the radiative kernel technique to show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
255
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(270 citation statements)
references
References 35 publications
14
255
1
Order By: Relevance
“…The primary model used in our study is the NCAR AGCM, Community Atmospheric Model version 4 (CAM4) [Gent et al, 2011;Bitz et al, 2012;Meehl et al, 2013]. We also provide results from CAM5 (S1) [Neale et al, 2010].…”
Section: Methodsmentioning
confidence: 99%
“…The primary model used in our study is the NCAR AGCM, Community Atmospheric Model version 4 (CAM4) [Gent et al, 2011;Bitz et al, 2012;Meehl et al, 2013]. We also provide results from CAM5 (S1) [Neale et al, 2010].…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with Stohl (2006), who found a large portion of modeled BC transport from fires as opposed to industrial sources. In general, biomass combustion aerosol has a much higher fraction of light-absorbing organic carbon (relative to BC) than does fossil fuel combustion (Bond et al, 2004), so it is very likely that the non-BC absorption reported by Doherty et al (2010) is from organics. If the non-BC particle fraction is significantly absorbing due to greater mass or greater absorption efficiency than that which has been assumed, then the net absorption from combustion sources may be underestimated.…”
Section: Constraints On Particle Parametersmentioning
confidence: 99%
“…Ocean heat flux is prescribed based on the climatology of a long pre-industrial control integration. This particular model configuration is described more fully in Bitz et al (2012). All of the results presented are for at least 60-yr equilibrium simulations, for which the last 30 yr have been averaged to create a climatology.…”
Section: Model Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…CESM (Bitz et al, 2011;Gent et al, 2011) has fully coupled atmosphere, ocean, land, and sea ice components. Within CESM, the Community Land Model v4.0 (CLM; Lawrence et al, 2011) receives the selected GLM outputs via a translator that converts these outputs to 16 CLM plant functional types (PFTs; eight forest, three grass, three shrub, one bare soil, and one crop) (Lawrence et al, 2012).…”
Section: Iesm Descriptionmentioning
confidence: 99%